Erythema nodosum leprosum masquerading as Sweet’s syndrome: a case report - Kazi, Seema A. (International Journal of Research in Dermatology, 2026)
Leprosy is a chronic disease caused by Mycobacterium leprae, primarily affecting skin and nerves. Over time the progression of leprosy may be disrupted by acute inflammatory episodes known as lepra reactions. Type 2 leprosy reactions also known as erythema nodosum leprosum (ENL), are characterized by painful red nodules on the skin, along with symptoms like fever, joint pain, malaise, and systemic complications. There have been reports of unusual clinical presentations of this condition such as bullous, pustular, ulceration, erythema multiforme‑like reaction, livedo reticularis, and Sweet’s syndrome (SS)‑like presentation. The pathogenesis of sweet’s-like ENL is still uncertain. It is believed that in SS a complex interaction of various cytokines leading to buildup of pro-inflammatory cytokines in the target tissues, which trggers an abnormal immune response to certain antigens. These findings may help explain the occurrence of such unusual lepra reactions. In this case, we describe an uncommon instance of type 2 lepra reaction in a 28-year-old man who had no prior diagnosis of leprosy. The condition presented similarly to SS‑like reaction and was diagnosed by slit skin smear and histopathological examination.